The Influence of Storytelling Activities and Self-Confidence on the Speaking Ability of Fifth-Grade Students at SD Muhammadiyah Makkoring - Abdul Rauf; Nuraini K; Yusmah; Jamaluddin Ahmad; Muhammad Hanafi; Jumiati (INTERACTION: Jurnal Pendidikan Bahasa, 2026)
This study aimed to determine the influence of storytelling activities and self-confidence on the speaking ability of fifth-grade students at SD Muhammadiyah Makkoring. This research employed a quantitative approach using a pre-experimental design in the form of a one-group pretest–posttest design. The population of this study consisted of all fifth-grade students at SD Muhammadiyah Makkoring, totaling 20 students. Since the population was relatively small, all students were selected as the research sample through total sampling. Data were collected through speaking ability tests, self-confidence questionnaires, observation, and documentation. The data were analyzed using descriptive and inferential statistics with the assistance of IBM SPSS Statistics software. The results showed that storytelling activities had a significant influence on students’ speaking ability. This was indicated by an increase in the students’ average speaking ability score from 61.35 in the pre-test to 79.65 in the post-test after the storytelling treatment was implemented. The t-test result showed a significance value of 0.000 < 0.05. Self-confidence also had a significant influence on students’ speaking ability, as indicated by an increase in the average score from 61.35 to 86.30 after self-confidence reinforcement was provided, with a significance value of 0.000 < 0.05. Furthermore, storytelling activities and self-confidence simultaneously had a significant influence on the speaking ability of fifth-grade students at SD Muhammadiyah Makkoring. Based on these findings, it can be concluded that storytelling activities and self-confidence can improve students’ speaking ability, both individually and simultaneously. Therefore, storytelling activities and self-confidence reinforcement can be used as alternative learning strategies to enhance elementary school students’ speaking ability